Detecção e classificação molecular de Chlamydophila psittaci em amostras fecais de aves assintomáticas - Braz, M.a. [UNESP] (2014)
Chlamydophila psittaci is a bacterium that causes respiratory or systemic disease in birds and humans. Owing to the risk of transmission from asymptomatic birds to humans, the objective of this study was to detect the presence of Chlamydophila spp. in asymptomatic birds. Four hundred and three fecal samples or cloacal swabs were collected from domestic, wild or exotic birds. The 403 samples were examined by real time PCR specific for the 16S subunit of rRNA gene using SsoFastEvaGreen®SupermixTM (Bio-Rad) and melting curve analysis. Hemi-nested PCR specific for the OMP-A gene, accomplished in real-time PCR positive samples, was followed by sequencing of the amplified fragments to determine the genotype of C. psittaci. Real-time PCR was positive in 17 (4.21%) samples. Hemi-nested PCR revealed positivity in two samples previously positive by real-time PCR. Sequencing of the fragment amplified by hemi-nested PCR allowed for the identification of genotype A of C. psittaci in one sample. The results of this experiment show that the real-time PCR targeting the 16S rRNA gene followed by melting curve analysis can be used for diagnosis of Chlamydophila sp. in fecal samples of asymptomatic birds. The classification of the Chlamydophila species and the genotype of C. psittaci must be accomplished by PCR targeting the ompA gene and sequencing of the amplified fragments.